Design, production and testing of a laboratory scale organic rankine cycle system - Kardaş, Onur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
This study presents the thermodynamic design, implementation and commissioning of a small scale organic Rankine cycle test rig. The objective was to design a exible organic Rankine cycle test rig to study performance of di erent working uids and cycle components. The test rig was instrumented with pressure, temperature and owmeter sensors to collect data from cycle operation. These data was used to validate various thermodynamic models. During the design process; environmental, safety and physical characteristics of 13 di erent uids were studied to obtain suitable working uids. Four uids namely R134a, R141b, R245ca and R245fa were taken into consideration for further detailed analyses. Maximum cycle e ciency and maximum net power output were considered as performance indicators. A recuperator was integrated into the system to investigate its e ect on the cycle e ciency. From the thermodynamic analyses, R134a was adopted as the working uid for the experimental setup. Detailed commissioning procedures were prepared and preliminary testing were conducted. Maximum net power output and maximum cycle e ciency were found to be 4.13 kW and 7.64%, respectively.
Keywords: Rankine cycle.